Effect of heating temperature and duration on the texture and protein composition of Bighead Carp (Aristichthys nobilis) muscle - Qixing Jiang; Jingwen Han; Pei Gao; Lixia Yu; Yanshun Xu; Wenshui Xia (International Journal of Food Properties, 2018)
The effect of heating temperature and duration on the texture and protein composition of bighead carp (Aristichthys nobilis) muscle was investigated. Samples were heated at 90°C, 100°C, 110°C, and 120°C for different times. The results showed that cooking loss increased significantly with increasing temperature and heating time, and a fractional conversion model was used to describe the increase. Hardness, chewiness, and gumminess exhibited a similar four-phase change with two peaks at 90°C, 100°C, and 110°C, and the trend was not observed at 120°C. Analysis of sodium dodecyl sulfate polyacrylamide gel electropheresis (SDS-PAGE) revealed that contents of myosin heavy chain decreased entirely to disappear and contents of actin significantly decreased. Increasing the intensity of the heavy molecular weight bands indicated the aggregation of myosin. Content of water-soluble proteins presented an increasing trend, which reflected the protein degradation and the release of low-molecular-weight compounds.